DAMPAK MAKANAN HARAM - Milhan, Milhan (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Allah commands His servants to consume halal and good food. Halal is everything that is permitted by Allah. Conversly, something that is categorized as subhat or unlawful must be avoided. In fact, everything that God has created for mankind is permissible unless there are instructions that state it is unlawful. Based on the word of Allah and the Sunnah, only a small portion of food is unlawful to consume. The Qur’an and Sunnah only explain in general about foods that are forbidden to eat. However, with the times and advances in food processing technology, more detailed rules are needed to regulate the food that is declared halal. In tis case, The government has issued Technical Guidelines for Halal Production Syastem and Law Number 33 of 2014 concerning Guantees for Halal Products. This technical manual and Law number 33 state that the halaness of food products is not only determined by the raw materials and mixed ingredients, but includes the halal process starting from the supply of goods, processing, storage, packaging, distribution and presentation. The unlawfulness of food affects one’s religion, soul and mind, one of which is if a person consumes prohibited food, then his request will be rejected because Allah is not pleased with him.